What Factors Affect the Choice of Accounting as a Career? The Case of Romania - Cristina-Florina Țicoi; Nadia Albu (Journal of Accounting and Management Information Systems (JAMIS), 2018)
This paper aims to examine the motivations of choosing accounting as a profession in Romania. The paper is motivated by the recent interest at the international level in understanding the trends in the accounting profession. The theoretical tension arises from the Romanian context given the significant challenges for the profession triggered by the transition from communism to a market-based economy. We use a survey-based approach. The sample consists of 112 students undertaking accounting courses both for Bachelor's Degree or Master Courses at two Romanian universities and 125 professionals belonging to The Body of Expert and Licensed Accountants of Romania. We find that the most important group of factors in choosing the accounting career includes the intellectual motivation, followed by relational and financial incentives. There are a few significant differences between men and women, and between students and professionals. When differences occur, women manifest a lower level of motivation, and professional accountants a higher level of motivation. The results show the driving forces behind the composition of the accounting profession and inform the sociology of the profession, of interest for both academia and practice. Our study contributes to an emerging national and international literature investigating the accounting profession by providing concrete information about the motivations of choosing it in Romania.
Keywords: M41; 650; accounting profession; motivation; Romania